A Trio Study Showing Novel Gene Mutation In LAMB3 Causing Junctional Epidermolysis Bullosa (Intermediate/ Severe) - Bandla, Shaile (Journal of Hereditary Diseases, 2024)
Background Junctional epidermolysis bullosa (JEB) is a type of Epidermolysis Bullosa, a group of genetic conditions that cause the skin to be very fragile and to blister easily. It is categorized into: the Herlitz type and the Non-Herlitz type. JEB is inherited in an autosomal recessive pattern. Most common genetic mutations associated are LAMB3, COL17A1, or LAMC2, and LAMA3 genes. Case presentation This study reports a consanguineous couple, carriers for pathogenic variant LAMB3 gene, with an affected child with a homozygous mutation in the LAMB3 gene causing Herlitz type of Junctional epidermolysis Bullosa/ Non-Herlitz type of junctional epidermolysis bullosa. Furthermore, prenatal diagnosis for the Gravida also showed the same pathogenic variant. Conclusion For autosomal recessive genetic conditions, it is advisable to perform a Trio whole-exome sequencing or next-generation sequencing to detect the genes associated with the disease. Depending on the type of variants involved prenatal diagnosis for the next pregnancy and treatment or management (if available) options can be offered/discussed.
Keywords: Junctional Epidermolysis Bullosa; Skin blistering; Trio-exome sequencing; LAMB3; Trio study; Autosomal recessive.